2017
DOI: 10.1111/mmi.13758
|View full text |Cite
|
Sign up to set email alerts
|

The two‐component response regulator Skn7 belongs to a network of transcription factors regulating morphogenesis in Candida albicans and independently limits morphogenesis‐induced ROS accumulation

Abstract: Skn7 is a conserved fungal heat shock factor-type transcriptional regulator. It participates in maintaining cell wall integrity and regulates the osmotic/oxidative stress response (OSR) in S. cerevisiae, where it is part of a two-component signal transduction system. Here, we comprehensively address the function of Skn7 in the human fungal pathogen Candida albicans. We provide evidence reinforcing functional divergence, with loss of the cell wall/osmotic stress-protective roles and acquisition of the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 126 publications
0
25
0
Order By: Relevance
“…It also included the induction of positive regulators of filamentation such as HWP1 , HGC1 , UME6 and BRG1 , and downregulation of the negative regulator of filamentation NRG1 ( Fig 7E and 7F ) . Finally, the HSF1 overexpression-specific targets encompassed genes known to be regulated by other morphogenetic regulators including the heat shock factor (HSF)-type transcription factors Sfl2 and Skn7[ 45 , 46 ]. These Hsf1-dependent morphogenetic regulators are ideal candidates for targets through which HSF1 overexpression could induce morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…It also included the induction of positive regulators of filamentation such as HWP1 , HGC1 , UME6 and BRG1 , and downregulation of the negative regulator of filamentation NRG1 ( Fig 7E and 7F ) . Finally, the HSF1 overexpression-specific targets encompassed genes known to be regulated by other morphogenetic regulators including the heat shock factor (HSF)-type transcription factors Sfl2 and Skn7[ 45 , 46 ]. These Hsf1-dependent morphogenetic regulators are ideal candidates for targets through which HSF1 overexpression could induce morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…UTH1 gene essentially takes part in oxidative stress regulation, and deletion of UTH1 gene will lead to extend the replicative lifespan of yeast [ 25 ]. SKN7 is upstream gene and is a stress response transcription factor in Saccharomyces cerevisiae [ 26 ]. Superoxide dismutases (SOD) are major ROS scavenging enzymes and can convert superoxide anion to hydrogen peroxide [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Skn7 is a conservative fungal heat shock factor-type transcriptional regulator that is part of a two-component signal transduction system. Previous studies have also revealed a close functional interaction between Skn7 and major morphogenetic regulators (including Efg1, Cph1, and Ume6), suggesting that Skn7 is part of the transcriptional pathway that controls filamentous growth of C. albicans [106].…”
Section: Cross Regulations Of Hyphal Developmentmentioning
confidence: 92%